PÉGON SCRIPT PHENOMENA IN THE TRADITION OF PESANTREN'S QUR’ANIC COMMENTARIES WRITING - Ahmad Baidowi (UIN Sunan Kalijaga Yogyakarta, 2020)
Relations that exist between the Qur'an and local traditions of society cause variations in the exegesis writing tradition. One of the reasons why there are variations is to make it easier for the public to understand the contents of the Qur'an. This is as happened in Javanese society, with the tradition of using the pégon script in exegesis writing. The pégon script is generally used by the Javanese as a medium for scientific transmission. Pegon script and pesantren is like the two sides of the coin that cannot be mutually separated. History shows, pégon becomes an important part in pesantren world civilization because the learning and intellectual works of pesantren are very dominant with the pégon tradition. This study uses a phenomenological approach as an effort to explain the phenomenon of the writing of the pégon in pesantren exegesis. This study concludes that the use of the pégon script in the writing of pesantren works such as Tafsir Al-Ibrīz fī Ma'ānī al-Qur'ān al-`Azīz by KH Bisri Mustafa, Al-Iklīl fī Ma`ānī al-Tanzīl by KH Misbah Mustafa Mustafa and Tafsir Al-Maḥallī by KH Mudjab Mahalli is not just a communication tool to convey the writer's message to the reader, however, more than that, it has educational functions in many ways. This can be seen in the use of the pégon script with the Gandul translation model. The use of the meaning of gandhul in the exegesis using pégon becomes a kind of Arabic-Javanese dictionary because the translation process uses the word for word model, so this makes it easier for Javanese people to understand the contents of the Qur'an. Besides that, the use of the pégon script in Javanese pesantren exegesis writing also functions as a medium for learning nahwu or Arabic grammatical system and also as a cultural identity of Javanese society.